(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
Objective: Acute otitis media (AOM) is a common reason for primary care visits in children. Yet, there is considerable debate over the most effective treatment. Therefore, we purpose to determine which is the best treatment for AOM. Methods: We conducted a systematic review and aimed to answer the following clinical questions: what are the main reasons for devolving AOM, how is its diagnosis, what are the clinical symptoms, and what are the effects of treatments in children with AOM? We searched Medline, PubMed, Scopus, Embase, The Cochrane Library, and other important databases. Result: We identified more than ten studies that fulfilled our inclusion criteria. We used GRADE to assess the quality of evidence for treatments. Conclusion: In this systematic review, we present information relating to the effectiveness and safety of the following interventions: the main etiological factors, the basic diagnostic analyses, analyses, and the successful treatment.